Combined antiviral therapy as effective and feasible option in allogenic hematopoietic stem cell transplantation during SARS-COV-2 infection: a case report - Vita, Serena; D’Abramo, Alessandra; Coppola, Andrea; Farroni, Chiara; Iori, Anna Paola; Faraglia, Francesca; Sette, Alessandro; Grifoni, Alba; Lindestam Arlehamn, Cecilia; Bibas, Michele; Goletti, Delia; Nicastri, Emanuele (Frontiers in Oncology, 2024)
Here we describe the case of a 51 years old Italian woman with acute lymphoblastic leukemia who underwent to hematopoietic stem cell transplantation (HSCT) during SARS-COV-2 infection. She presented a prolonged COVID-19 successfully treated with dual anti SARS-COV-2 antiviral plus monoclonal antibody therapy.